The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.energyfuels.2c01059
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Advances in the Catalytic Desulfurization and Denitrogenation of Transportation Fuel Oils Using Graphitic Carbon Nitride and Boron Nitride

Abstract: Expulsion of sulfur-containing compounds as well as nitrogen-containing compounds present in fuel oils is critical because it can cause numerous environmental problems and catalyst deactivation. Because of the limitations of the other catalysts and adsorbents used for desulfurization, a new type of carbon material, i.e., graphitic carbon nitride (g-C3N4), has emerged. It is similar in morphology to graphene having a two-dimensional structure and possessing a band gap of 2.7 eV and is an attractive catalyst att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 146 publications
(201 reference statements)
0
10
0
Order By: Relevance
“…have been utilized over the past several decades to activate and cleave C–S bonds. However, these catalytic systems are expensive and often suffer from poor chemoselectivity, low catalytic efficiency, and low recyclability which greatly limits their long-term use as desulfurization catalysts …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…have been utilized over the past several decades to activate and cleave C–S bonds. However, these catalytic systems are expensive and often suffer from poor chemoselectivity, low catalytic efficiency, and low recyclability which greatly limits their long-term use as desulfurization catalysts …”
mentioning
confidence: 99%
“…However, these catalytic systems are expensive and often suffer from poor chemoselectivity, low catalytic efficiency, and low recyclability which greatly limits their long-term use as desulfurization catalysts. 16 Recently, our lab has shown that a covalent organic framework (COF) 17−19 containing dehydrobenzoannulene (DBA)-Ni(0) complexes can be used to reductively cleave the C(aryl)-S bonds of several organosulfur compounds utilizing hydrosilanes as the reducing agent. 20 While this catalytic system was recyclable and great for activating C(aryl)-S bonds of fused and unfused aryl thioethers, it is still unclear if this Ni(0)-based catalytic system is useful for the desulfurization of dibenzothiophenes (DBTs), a class of refractory sulfur compounds that are commonly found in sour crude oil.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of agglomeration is an urgent matter to be solved, as is the case with other TMOs. A feasible strategy is to select an appropriate porous carrier to construct supported catalysts. , Carbon nitride (g-C 3 N 4 ) has a simple preparation process and high yield and is often used as a carrier in supported catalysts . In comparison, three-dimensional porous carbon nitride (3D g-C 3 N 4 ) obtained by the supramolecular assembly method, with a rich pore structure and high specific surface area, is a more suitable carrier …”
mentioning
confidence: 99%
“…6,7 Carbon nitride (g-C 3 N 4 ) has a simple preparation process and high yield and is often used as a carrier in supported catalysts. 8 In comparison, three-dimensional porous carbon nitride (3D g-C 3 N 4 ) obtained by the supramolecular assembly method, with a rich pore structure and high specific surface area, is a more suitable carrier. 9 Ionic liquids (ILs) have many excellent properties, which have been widely studied by researchers since their discovery.…”
mentioning
confidence: 99%